Aesthetics and Philosophical Poetics - Kačerauskas, Tomas (Problemos, 2002)
In closed aesthetics theory the author brings out philosophical poetics. Philosophical poetics is both narrower and broader than aesthetics because it is supported with poetical fomis but has ethical and existential aspirations.
Keywords: aesthetics; piece of art; philosophical poetics; hermeneutics